SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH: BEST PRACTICE PADA PEMERINTAH DAERAH DIY - Topaz Mardiarto (ABIS: Accounting and Business Information Systems Journal, 2018)
The accountability of Local Government performance in Indonesia is low. This fact is based on the accountability system evaluation result conducted by Ministry of Administrative and Bureaucratic Reform (Kemenpan RB). Special Region of Yogyakarta (Daerah Istimewa Yogyakarta) Local Government in the last three years has become a region with the highest mark so that it becomes a reference for another region. The aim of this research is to formulate the best practice in the implementation of accountability system of government institution performance in DIY Local Government in order to be utilized by another region/institution.            The informants of this research were those directly involved in the implementation of performance accountability systems in DIY Local Government comprising of Bappeda (Development Planning Board), Inspectorate, Organization Agency, and evaluator Kemenpan RB. Theory employed in this research is logic model theory to analyze performance planning and Friedman’s four quadrants to analyze performance measurement.            The research result shows that a good performance accountability system must start from a good planning element. Planning system at least fulfill result oriented, alignment, interrelated causality, and synergetic criteria. Every constituted performance must have an indicator in order to be able to measure the achievement. In a good measuring system, every indicator must be able to be shown and accounted for to the society. To support the overall accountability system, e-government innovation must be used to facilitate implementation, monitoring, and  evaluation of activities.